1991
DOI: 10.1111/j.1476-5381.1991.tb12453.x
|View full text |Cite
|
Sign up to set email alerts
|

The presence of five cyclic nucleotide phosphodiesterase isoenzyme activities in bovine tracheal smooth muscle and the functional effects of selective inhibitors

Abstract: 1 The profile of cyclic nucleotide phosphodiesterase (PDE) isoenzymes and the relaxant effects of isoenzyme selective inhibitors were examined in bovine tracheal smooth muscle. The compounds examined were the non-selective inhibitor 3-isobutyl-1-methylxanthine (IBMX), zaprinast (PDE V selective), milrinone and Org 9935 (4,5-dihydro-6-(5,6-dimethoxy-benzo[b]thien-2-yl)-5-methyl-1(2H)-pyridazinone; both PDE III selective), rolipram (PDE IV selective) and Org 30029 (N-hydioxy-5,6-dimethoxy-benzo[b]-thiophene-2-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
2
2

Year Published

1993
1993
2005
2005

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 23 publications
4
52
2
2
Order By: Relevance
“…It is well known that PDE4 is specific for the hydrolysis of cAMP [3]. It has been reported that rolipram (type 4 inhibitor) relaxed bovine trachea by an increase in the cAMP content [19]. In the present study, there was a positive correlation between the inhibition of CCh-induced contractions and the increase in cAMP content elicited by Ro20-1724 in the gall bladder.…”
Section: Discussionsupporting
confidence: 68%
“…It is well known that PDE4 is specific for the hydrolysis of cAMP [3]. It has been reported that rolipram (type 4 inhibitor) relaxed bovine trachea by an increase in the cAMP content [19]. In the present study, there was a positive correlation between the inhibition of CCh-induced contractions and the increase in cAMP content elicited by Ro20-1724 in the gall bladder.…”
Section: Discussionsupporting
confidence: 68%
“…Pharmacological characterization of PDE3 has been greatly facilitated by the development of potent, highly selective inhibitors of this isoform, such as SK&F 94836 (siguazodan) [60] and Org 9935 [61]. We found that SK&F 94836 and Org 9935 were very potent inhibitors of rat islet PDE activity, especially in membrane fractions [57] with up to 85% of membrane-bound PDE being inhibited with IC 50 values of 5.5 and 0.05 µmol/l respectively.…”
Section: Pde3mentioning
confidence: 92%
“…However, in aorta, milrinone, a PDE3 inhibitor, inhibited norepinephrine-induced contraction more potently than Ro20-1724, a PDE4 inhibitor (36). On the other hand, rolipram, a PDE4 inhibitor, inhibited methacholine-or histamine-induced contraction more potently than milrinone in bovine trachea (37). In addition, AH 21-132, a papaverine derivative compounds, inhibited PDE4 (cAMP-specific PDE) more selectively than other PDEs in bovine tracheal smooth muscle (38).…”
Section: Effects Of Papaverine On Pcr and Atp Contentsmentioning
confidence: 95%